1975
DOI: 10.1111/j.1550-7408.1975.tb05851.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Division in the Ameboflagellate Adelphamoeba galeacystis

Abstract: Nuclear division is synchronized cultures of the ameoboflagellate Adelphamoeba galecystis has been described. Division in this organism is typically promitotic. It occurs within an intact nuclear membrane and is characterized by the persistence of the nucleolus and its transformation into 2 polar masses. The nucleolus is stained with pyronin-Y by the methyl green pyronin-Y technic, and with Heidenhain's hematoxylin, but is unstained by the Feulgen reaction. The reaction with these stsins is removed after diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Fibrous 1). 5,12). The polar masses stained densely; they were Dor crescent-shaped, with the flattened side facing the chromatin (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrous 1). 5,12). The polar masses stained densely; they were Dor crescent-shaped, with the flattened side facing the chromatin (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Rafalko (8) did not discuss vacuolations in early promitosis of Naeglaria gruberi nor did he (9) discuss them in early promitosis of Tetramitus rostratus, although he illustrated them in plates of both amebae. Considering the dynamic nature of the nucleolus, we hesitate to place as much emphasis on the vacuolations as did Napolitano & Smith ( 5 ) . They suggested that the portion of the nucleolus that is reduced during nucleolar vacuolation may participate in the synthesis of the interzonal body.…”
Section: Discussionmentioning
confidence: 97%